2014
DOI: 10.1016/j.cmet.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

AMPK at the Nexus of Energetics and Aging

Abstract: When energy supply is low, organisms respond by slowing aging and increasing resistance to diverse age-related pathologies. Targeting the mechanisms underpinning this response may therefore treat multiple disorders through a single intervention. Here we discuss AMP-activated protein kinase (AMPK) as an integrator and mediator of several pathways and processes linking energetics to longevity. Activated by low energy, AMPK is both pro-longevity and druggable, but its role in some pathologies may not be beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
340
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(347 citation statements)
references
References 184 publications
(240 reference statements)
6
340
0
1
Order By: Relevance
“…(Hardie et al ., 2012). Moreover, the result from Burkewitz et al ., 2014 is also interesting. It suggests that sustained stimulation of AMPK lead to irreversible senescence, while acute activation of AMPK catabolic pathway permitted a rapid adaptation or resistance to external and internal stresses (Burkewitz et al ., 2014).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…(Hardie et al ., 2012). Moreover, the result from Burkewitz et al ., 2014 is also interesting. It suggests that sustained stimulation of AMPK lead to irreversible senescence, while acute activation of AMPK catabolic pathway permitted a rapid adaptation or resistance to external and internal stresses (Burkewitz et al ., 2014).…”
Section: Discussionmentioning
confidence: 95%
“…To explore the status of autophagic flux, we applied several reliable assays (Mizushima et al ., 2010; Klionsky et al ., 2012), such as evaluating the Cathepsin B protein level, measuring the acid phosphatase activity, and comparing the influence of a lysosome inhibitor on the p62 accumulation. We also assessed the inhibition of GFP‐LC3 fluorescence using a GFP‐RFP‐LC3‐expressing cell, and obtained consistent data with previous report (Burkewitz K et al ., 2014), indicating that AMPK activation can improve the autophagic activity in cells with H 2 O 2 ‐induced senescence. Particularly, we explored the effects of AMPK activation on the late stage of autophagy, especially on the function of lysosomes, which is different from previous studies that concentrated on the role of AMPK in the early stage of autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current biomedical strategy has developed significantly to target the unique proximal causes of the pathologies to alleviate the signs of HS. 15 For example, crystalloid and colloid are infused to supplement the blood volume during HS, and NaHCO 3 is used to treat metabolic acidosis. 16 However, these strategies treat each of the pathologies separately, 15 and a resuscitation strategy that provides multiple therapeutic effects may be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (2004) found no suppression of reproduction with life extension by resveratrol in Drosophila and C. elegans. Resveratrol upregulates effectors of dietary restriction like sirtuins and AMPK (Baur et al 2006;Burkewitz et al 2014). Grandison et al (2009) found that dietary restriction extended life span and reduced reproduction of Drosophila, but augmenting methionine restored reproduction without reducing life extension.…”
Section: Trade-offs and Life Extensionmentioning
confidence: 99%